2022
DOI: 10.1001/jama.2022.18346
|View full text |Cite
|
Sign up to set email alerts
|

Moving to More Evidence-Based Primary Care Encounters

Abstract: This Viewpoint discusses ways in which free time during patient visits, resulting from removal of tradition- and reimbursement-driven care in favor of more evidence-based care, could be used to achieve better health outcomes based on recommendations from the US Preventive Services Task Force evidence-based preventive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As early as the 1860s physicians noted that performing a complete symptom inventory was so time‐consuming as to make it impracticable. Studies stretching back 80 years have found that performing a comprehensive ROS takes an average of 15 min—time few clinicians have to spare 7,9,10 …”
Section: Rise Of the Rosmentioning
confidence: 99%
“…As early as the 1860s physicians noted that performing a complete symptom inventory was so time‐consuming as to make it impracticable. Studies stretching back 80 years have found that performing a comprehensive ROS takes an average of 15 min—time few clinicians have to spare 7,9,10 …”
Section: Rise Of the Rosmentioning
confidence: 99%
“… We continue to document based on reimbursement and tradition rather than scientific evidence. In their essay subtitled “A farewell to the review of systems,” Barry and Tseng argue for deleting the traditional review of systems and that documentation should be based on scientific evidence ( 17 ). …”
Section: Why Are Our Notes So Bulky?mentioning
confidence: 99%